Finite Element Analysis of Thermal Effects in Diode End-Pumped Solid-State Lasers. (10th April 2017) - Sayem El-Daher, Moustafa
Abstract : Thermal effects are the main obstacle to getting high power and good beam quality in diode end-pumped solid-state lasers. In this work, a theoretical investigation of thermal effects in single and dual end-pumped solid-state lasers is carried out using finite element analysis (FEA) for a selected number of widely used laser producing materials, namely, Nd:YAG, Yb:YAG, and Nd:KGW. Crystals with different dimensions are also investigated both in single and in dual end-pumped configuration. Finally, the effect of using composite crystals on thermal lensing is investigated. An experiment to measure the thermal focal length for two different crystals was carried out and a comparison with FEA computed focal length of the thermal lens is made. In all cases studied in this work, results show clear effects of thermal lensing with some differences depending on crystal type, pump power, and size.